Living with Loss: Survival and Recovery among Conflict Widows in Bener Meriah, Aceh - Irwan, Irwan; Hasanah, Ida; Arfan, Fahmi; Fitriani, Fitriani; Fatianda, Septian; Nur, Muhammad; Sakiya, Nur; Alafanda, Irdan (Jurnal Sosiologi Agama Indonesia (JSAI), 2025)
This study examines the lived experiences of widows affected by the early-2000s horizontal conflict in Timang Gajah, Bener Meriah, Aceh. While conflict research has frequently emphasized armed actors, patterns of violence, and political processes, less attention has been directed toward how violence is experienced and managed within everyday household life, particularly by widows. This article addresses that gap by focusing on how women navigated the loss of husbands, sustained family survival under conditions of insecurity, and gradually reconstructed social and economic stability. The study applies a historical approach with a qualitative descriptive design. Data were collected through field observation, in-depth interviews, and focus group discussions. The main empirical material derives from narrative accounts provided by five widows. The analysis centers on three interrelated dimensions: the chronologies of loss, survival practices in everyday life, and processes of psychological recovery. The findings show that widowhood in conflict settings constitutes an extended social condition rather than a singular moment of bereavement. Uncertainty surrounding disappearance, economic instability, and fear shaped the widows’ post-loss experiences. Survival was negotiated through locally available livelihoods, kinship support, and women’s communal solidarity networks. Psychological recovery emerged as a gradual process grounded in relational support, everyday routines, and religious meaning-making rather than formal therapeutic intervention. These narratives demonstrate how survival and recovery are continuously negotiated within the social organization of everyday life in conflict-affected communities.